Robust clicked assembly based on iron oxide nanoparticles for a new type of SPR biosensor. Issue 34 (2nd July 2018) - Dolci, Mathias; Bryche, Jean-François; Leuvrey, Cedric; Zafeiratos, Spyridon; Gree, Simon; Begin-Colin, Sylvie; Barbillon, Gregory; Pichon, Benoit P.
Abstract : A novel strategy to create an original nanostructured SPR biosensor with enhanced sensitivity is reported. Iron oxide nanoparticle assemblies with tunable structure and decorated with bio receptors were grafted onto gold thin films by taking advantage of "click" chemistry. Abstract : We present a novel strategy to create an original nanostructured SPR biosensor with enhanced sensitivity. Our approach consists of using high refractive index dielectric materials to increase the sensitivity factor of a gold thin film despite its large evanescent electromagnetic field decay lengths. Iron oxide nanoparticles were grafted onto a gold thin film and were easily functionalized by biomolecular receptors through a two step copper catalyzed alkyne–azide cycloaddition (CuAAC) "click" reaction. This strategy allowed us to prepare a highly stable and robust nanostructured biosensor. We selected the very-well known biotin–streptavidin couple to demonstrate the efficiency of our strategy toward the enhancement of the detection of biomolecules without using any labelling of the target molecules. High refractive index nanoparticles were demonstrated to enhance markedly the sensitivity to the detection of streptavidin by increasing the sensitivity factor of the gold thin film and the accessibility of biotin groups (reduction of steric hindrance).